2011
DOI: 10.1128/jcm.02057-10
|View full text |Cite
|
Sign up to set email alerts
|

JC Virus Variant Associated with Cerebellar Atrophy in a Patient with AIDS

Abstract: The human polyomavirus JC virus (JCV) is the agent of progressive multifocal leukoencephalopathy (PML).It has also recently been involved in cerebellar atrophy. Factors involved in this entity are elusive. We present a case of a human immunodeficiency virus (HIV)-infected patient with PML and cerebellar atrophy. In addition to a compartmentalization of JCV strains between urine, cerebrospinal fluid, and cerebellum, specific rearrangements in the JCV regulatory region were observed in the cerebellum, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…On sequencing viral DNA in a later study on the same brain samples [27], Dang and Koralnik showed a deletion in the C-terminal portion of the VP1 gene, which encodes for the major capsid protein. Other mutations have been described in other patients, in the VP1 gene [11,20,22] or in the regulatory region [12], and several strains of JCV can be found in the same patient [20,2]. The different alleles are thought to change the receptor specificity of the virus for different peripheral cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On sequencing viral DNA in a later study on the same brain samples [27], Dang and Koralnik showed a deletion in the C-terminal portion of the VP1 gene, which encodes for the major capsid protein. Other mutations have been described in other patients, in the VP1 gene [11,20,22] or in the regulatory region [12], and several strains of JCV can be found in the same patient [20,2]. The different alleles are thought to change the receptor specificity of the virus for different peripheral cells.…”
Section: Discussionmentioning
confidence: 96%
“…The frequency of JC-GCN seems to be low: Dang et al [11] reported virologic results for 4 new patients in 2012 and reviewed 10 reported cases. Since then, Roux et al [12] and Shang et al [13] reported 1 more case each, and Wijburg et al [14] described 2 more cases in 2014. Adding our 5 cases leads to a total of 23 reported cases (22 probable and 1 possible).…”
Section: Discussionmentioning
confidence: 96%
“…A more recent case involving an AIDS patient with cerebellar atrophy also showed rearrangement of the NCCR, also with a type IS/IIS arrangement (with no sequence block "b" and only a partial piece of block "d"). Comparison of CSF-isolated virus and cerebellar virus NCCRs showed differences and changes in transcription factor binding sites (426). Thus, it appears that alternative transcription factor binding sites may play a role in JCV-GCN, further demonstrating the importance of the NCCR sequence in JCV cell type specificity.…”
Section: Jc Virus Granule Cell Neuronopathy and Other Jcvassociated Nmentioning
confidence: 90%
“…If the VP1 truncations can be confirmed as a specific virus determinant associated with or selected in this pathology in independent studies, a convincing hypothesis and its experimental testing still needs to be put forward (162,229). In another report, no major alterations of the C-terminal VP1 were found, except for amino acid changes at methionine-339 to isoleucine, and lysine-345 to arginine (230). The NCCR was rearranged with a partial deletion of the D-and B-block, whereas the CSF variant only showed a partial D-block deletion as signature rearrangement (230).…”
Section: Jcpyv Diseasementioning
confidence: 99%
“…In another report, no major alterations of the C-terminal VP1 were found, except for amino acid changes at methionine-339 to isoleucine, and lysine-345 to arginine (230). The NCCR was rearranged with a partial deletion of the D-and B-block, whereas the CSF variant only showed a partial D-block deletion as signature rearrangement (230). The histopathology showed LTag expression in neuronal cells staining positive for MAP-2 in the granule cell layer (228,231).…”
Section: Jcpyv Diseasementioning
confidence: 99%